On-line and off-line solutions in the precision weed control - Reisinger, Péter (Acta Agraria Debreceniensis, 2012)
There are two directions of the development of the methods in precision weed controll. One is the on-line, either is the off-line solutions. The advantige off the on-line method is that it covers all the territory of the field, therefore there are no problems in sampilng methodology. At the same time picture processing is slow and the performance of the machines is low. We have choosen the off-line precision weed controll in Hungary to start with and we have solved the precision wedd controll of wheat, maize and sunflower successfully. We have also conducted on-line developments with the application of Weed Seeker sensor.